2006
DOI: 10.1093/ecam/nel067
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Static Magnetic Field for Locomotor Activity of Experimental Osteopenia

Abstract: In order to examine the effectiveness of applying a static magnetic field (SMF) for increasing bone mineral density (BMD), we assessed the degree of osteopenia by dual-energy X-ray absorptiometry (DEXA), the metabolism measuring system, and histological examination of bone tissue in an ovariectomized (OVX) rat model. Thirty-six female Wistar rats (8 weeks old, 160–180 g) were divided into three groups. The rats in the OVX-M group were exposed to SMF for 12 weeks after ovariectomy. The ovariectomized rats in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
0
7
1
1
Order By: Relevance
“…We have investigated the effects of moderate intensities of SMFs (15 mT) using permanent magnets on bone formation during implant osseointegration in the rabbit tibia model, the rabbit being the most suitable small animal model for testing implants (International Standard ISO 10993-6, 2007). Although most in vivo studies have been performed in rat models, the intensities of the SMFs used were 2-12 times higher than in our study (Taniguchi et al 2004;Puricelli et al 2006Puricelli et al , 2009Taniguchi & Kanai 2007;Xu et al 2011). 15 mT has been found to be effective in speeding up integration between implant and bone in vivo (Leesungbok et al 2013) and in promoting the proliferation and differentiation of MSCs in vitro (Kim et al 2015).…”
Section: Discussioncontrasting
confidence: 52%
“…We have investigated the effects of moderate intensities of SMFs (15 mT) using permanent magnets on bone formation during implant osseointegration in the rabbit tibia model, the rabbit being the most suitable small animal model for testing implants (International Standard ISO 10993-6, 2007). Although most in vivo studies have been performed in rat models, the intensities of the SMFs used were 2-12 times higher than in our study (Taniguchi et al 2004;Puricelli et al 2006Puricelli et al , 2009Taniguchi & Kanai 2007;Xu et al 2011). 15 mT has been found to be effective in speeding up integration between implant and bone in vivo (Leesungbok et al 2013) and in promoting the proliferation and differentiation of MSCs in vitro (Kim et al 2015).…”
Section: Discussioncontrasting
confidence: 52%
“…As in these studies on bone tissues, most cellular experiments and studies of animal models showing either osteogenic or antiresorbtive effects of SMFs are not simulating the effects of chronic exposure to SMFs on bone but rather revealing relatively stationary effects of nearby SMFs [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 ]. Recently, Aïda et al , [ 30 ] exposed rats in plexiglass cages to SMFs of 128 mT for 1 h per day for 5 consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies about the effects of SMFs on the skeleton is at the cellular level or is applied to animal models [ 6 , 7 ]. Almost all evidence from these studies suggests either beneficial effects or no harmful bio-effects of SMFs on bone health [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, most of these animal studies in rodents and research at the cellular level evaluating the effects of SMFs on the skeletal system have often been complicated by creating pure SMFs in vivo and simulating this chronic exposure due to relative movement between the magnet and bone in real life.…”
Section: Introductionmentioning
confidence: 99%
“…Taniguchi et al . [ 120 , 121 ] investigated the effects of 30 mT static magnetic field on the bone mineral density of ovariectomized rat model under whole body exposure. The results indicated that bone mineral density was significantly increased after 12 weeks because static magnetic field increased the level of locomotor activity in rats model.…”
Section: In Vivo Studies Of Physical Stimulatiomentioning
confidence: 99%
“…The static magnetic field and pulse electromagnetic field were widely used in the treatment of various bone-related diseases such as fracture, osteoporosis, bone delayed union or nonunion, etc ., owing to their non-invasive, no infection, no side effects and ease of use[ 120 , 126 , 138 ]. In vivo studies, many researchers implanted magnet rods, magnetic plates and magnetic washers into bone defect sites to construct static magnetic field[ 118 , 121 - 124 , 139 , 140 ]. Some researchers constructed static magnetic field stimulation equipment composed of magnetic plates which fixed on outside of cage ( Figure 8A )[ 120 ] or utilized signal generator to produce direct current which transferred to a pair of Helmholtz coils to expose animals[ 141 ].…”
Section: The Equipments Of Physical Stimulation Systemsmentioning
confidence: 99%